BMI and Physical Activity with Cardiovasculer Fitness and Quality of Life of Health Vocational Students at the University of Bengkulu - Kurniati, Neng; Fitri Ramadhaniati; Linda Yulyani (JURNAL KEBIDANAN, 2025)
Health vocational students are generally in the late adolescent phase, aged 17-21 years, which implicitly acts as a role model for healthy individuals. Quality of life in adolescents is influenced by various factors including physical health, psychological health, self-perception, parental relationships, finance, environment, and social relationships. Striving for a quality life for the younger generation as the nation's hope is essential and determines the reproduction process of the next quality generation. Indonesia has a triple burden of nutritional problems namely stunting, wasting, and obesity as well as micronutrient deficiencies such as anemia. Body Mass Index (BMI) is one indicator of nutritional status that can be assessed in adolescents. The prevalence of adolescent physical activity from year to year tends to decrease. This study aims to explain the relationship of BMI and physical activity with physical fitness and quality of life of Health Vocational Students at Bengkulu University. Methods: This study is a quantitative descriptive study with a cross-sectional approach, the subjects were health vocational students of Bengkulu University. The results showed no correlation between BMI and fitness and quality of life (p > 0.05), there was a weak correlation between physical activity with cardiovascular fitness (p= 0.028, r = -0.161), and quality of life of UNIB health vocational students (p = 0.043 and r = 0.148). There is a very strong correlation between fitness and quality of life (p = 0.000, r = -0.926).